Trade policy and performance in Sub-Saharan Africa since the 1980s - Charles Ackah; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2005)
This paper reviews trade policy reform and performance in Africa since the 1980s. African countries have implemented significant trade liberalisation in this period, in particular reducing tariffs. This has usually resulted in an increase in imports, but export growth has often been sluggish so that in many countries the trade deficit has increased. The paper documents trends and performance and reviews the explanations for poor export response. While trade policy reform has been beneficial, the impact has not been as great as expected and the core challenge facing African countries is how to diversify and increase exports.
Keywords: 330